Ukraine one year later: Impacts on global food security - Glauber, Joseph (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The outbreak of war between two of the world’s key agricultural producers jeopardized more than a third of world wheat trade, 17% of world maize trade, and almost 75% of world sunflower oil trade. Within a week of the invasion, prices of wheat futures had jumped almost 60%, while corn and soybean prices were up over 15%. Yet as the war continued through 2022, international markets adjusted and adapted, and—while high prices and other problems persist—the worst-case scenarios for agricultural trade and food security were largely averted. The main lesson of 2022 is that global markets have generally worked well when not impeded by government actions like export restrictions. Hopefully that will be a lesson learned for countries as the world enters another year of global impacts from the war in Ukraine